Edukasi dan Pendampingan Keluarga dalam Upaya Cegah Perundungan di Kota Depok - Ritanti, Ritanti; Permatasari, Indah; Siregar, Tatiana (Poltekita: Jurnal Pengabdian Masyarakat, 2024)
Bullying is a complex and urgent problem. The incident is difficult to control and makes parents anxious. Family education and assistance is a service effort to the community to prevent bullying among teenagers through education and family assistance to the community in Limo Depok District. The priority problems currently faced by partners are the lack of information and knowledge related to bullying and the lack of programmed educational and mentoring activities as well as coaching youth and families related to bullying. This PKM aims to provide knowledge and understanding for families and teenagers regarding bullying and efforts to prevent it. The solution and method for implementing this PKM is through a series of activities: (1) Community meetings; (2) Preparation of media and guidebooks; (3) Communication, information, and health education (KIE) related to bullying; (4) Family assistance; (5 )Supervision and evaluation of activities. The results of this PKM activity prove that education and family assistance are effective in increasing knowledge (69.2%), attitudes (53.8%), and behavior (57.7%) of families and teenagers regarding bullying. In conclusion, the PKM program can act as a promotive and preventive medium in creating a harmonious and loving family environment and can shape the strong character of the nation's children.